Contemporary approach to online education at the medical school applying Socratic seminar or Socratic circle to lecturing - K. Shumilina; S. Kornienko; D. Lapshin; R. Vastyanov (Kazimierz Wielki University, 2022)
We have sought the answer to a problem of online education introduced by COVID-19 pandemic. We suppose online education is to be the most dynamic form of professional learning which takes place at a distance with the use of effective informational and communicative tools. Our objective was to be focused on solving specific professional issues, to create conditions for effective learning based on our professional experience, with its maximum use. Socratic Dialogue is a brand that symbolizes the improvement of the quality of thinking in clarifying and solving problems in questioning in the community. Socratic seminars are one of the pedagogical technologies that provide the opportunity for students to actively practice in a wide variety of academic and professional skills. Its systematic procedure is used to examine a text through questions and answers founded on the beliefs that all new knowledge is connected to prior knowledge, that all thinking comes from asking questions, and that asking one question should lead to asking further questions. The goal of this study was to have participants work together, seek and gain deeper understanding of concepts in the text through thoughtful dialogue rather than memorizing information that has been provided for them. Our focus was to explore multiple perspectives on a given issue or top and student's decision-making for the clinical cases provided. The method has helped us to identify students which lack any concrete knowledge or are not able to implement theoretical knowledge into solving practical tasks. The method also improved creative and critical and clinical thinking of the students who were actively engaged in the process not only during the class but also by preparing effectively for the class. We prioritized flexibility, individualization of learning, and put emphasis on self-study of the students. The authors voluntary move away from the truly philosophical direction in the introduction of Socratic dialogue into the methodology of modern teaching students in medical and biological disciplines and implement this learning option as an auxiliary one in online learning. Finally, authors analyzing the efficacy of a new teaching methodology in which the initiative of the conversation, its directions and possible branches from the original premise are provided to the students themselves.